The Influence of Turnover Intention, Rewards, Leadership, and Work Targets on Employee Performance: A Study at Marwa Group Indonesia Wonosobo - Ana Siyamita; Bahtiar Efendi; Muhamad Asif Maulana Akbar (Moneter: Jurnal Keuangan dan Perbankan, 2026)
This study examines the effects of turnover intention, reward systems, leadership, and performance targets on employee performance at Marwa Group Indonesia in Wonosobo. It investigates both the partial and simultaneous effects of these variables and identifies the factor exerting the strongest influence on employee performance. A quantitative approach with a survey design was employed. Data were collected through questionnaires distributed to all 39 employees of Marwa Group Indonesia in Wonosobo using a census sampling technique. The data were analyzed using multiple linear regression with SPSS, following validity and reliability testing and classical assumption tests. The results indicate that turnover intention, reward systems, leadership, and performance targets have positive and statistically significant effects on employee performance, both individually and collectively. The adjusted R-squared value of 0.583 indicates that 58.3% of the variance in employee performance is explained by the four independent variables, while the remaining 41.7% is attributable to factors outside the research model. Based on the standardized beta coefficients, turnover intention emerged as the most influential variable, followed by performance targets, reward systems, and leadership. This finding differs from much of the previous literature, as turnover intention in the context of Marwa Group Indonesia appears to reflect employees’ career-development orientation rather than a decline in organizational commitment. This pattern may be associated with the characteristics of the workforce, which is predominantly composed of working-age employees, contract-based personnel, and employees with relatively short organizational tenure. The findings suggest that improving employee performance requires an integrated human resource management approach involving strengthened reward systems, effective leadership, clearly defined performance targets, and appropriate employee retention and career-development strategies.